Educational inspection techniques: start premise - Pérez Aguilar, José Francisco (Avances en Supervisión Educativa, 2013)
The education inspectorate carries out its functions and responsibilities in the field of educational administration concerned, his speech being subject to a strong specialization from two points of view. On the one hand, raised from specific areas of work, subject to a performance interchangeably in different teachings and levels that make the educational system, and, secondly, using techniques imported from the field of educational research appropriate to the aspects of educational inspection.The article proposes a possible correlation of the powers of inspection in some of the techniques of educational research, supporting them with evidence collected from the Andalusian action plans, collected recently in the Portal Educational Inspection of Andalusia, facilitating access and therefore the study. It also addresses the definition and types of triangulation, since the application of techniques yields a wealth of information to be reliable and valid, should be subjected to such a process, to the extent that is possible and feasible to inspection education.
Keywords: educational inspection; powers; actions; intervention; educational research; techniques; triangulation